Negotiating the Democratic Paradox: Approaches Drawn From Governance Efforts on Yellowstone River - Horton, Cristi C.; Gilbertz, Susan J.; Hall, Damon M.; Peterson, Tarla Rai (Frontiers in Communication, 2019)
We propose to analyze perspectives on watershed governance articulated by community leaders along the Yellowstone River (Montana, U.S.A.). These leaders framed watershed governance as a process of negotiating tensions between individual rights and equality, embracing diverse viewpoints, and acknowledging the constant presence of change. We used informant directed interviews, and analyzed the resulting discourse from the theoretical perspective of Chantal Mouffe’s democratic paradox, which provides insight into governance dynamics and suggests ways to provide more meaningful engagement opportunities for all participants. The paradox between liberty and equality is both difficult and important for civic leaders to negotiate. Failure to recognize the centrality of this paradox encourages practices that attenuate democracy and lead to either autocracy, where a single individual or party controls all important political matters, or mobocracy, where lawlessness and chaos prevail. These civic officials struggled to develop a pluralistic democracy that could legitimize heterogeneous perspectives of residents. Their version of pluralistic democracy offers a model for negotiating the democratic paradox. It is critical for democratic governance to build approaches to orderly change into a political system. These leadership struggles offer lessons regarding ways to position all citizens inside the borders where moral values and rules of fairness apply.